Challenges and opportunities for micro finance institutions during COVID-19 - Sharma, Ashish; Veena Singh (American Journal of Economics and Business Management, 2020)
ABSTRACT COVID-19 (Coronavirus) has unambiguously indoors within the developing nations. Thousands of patients are found and reported diagonally on planet. Many countries across the planet including India announced that they might enter lockdown for a few periods; in India initially, it had been for three weeks with poorly equipped health-care systems to deal with pandemic, there are lots of reasons to consider that the cost of the coronavirus within the developing nations are going to be still extra harmful than that within the developed nations, with higher death rates. On the other hand, we observed very little facts and figures that the worldwide microfinance community has awakened to complete degree of the disaster because the virus spreads and grasps very fast in developing nations across the world. The international community of microfinance deploy to respond and answer to the COVID-19 catastrophe; now we would like to require taking some major and important steps as to make sure the universal microfinance industry that gives micro financial products and services to the necessitous person should not be left behind. If the microfinance service goes to survive during this tough time, we would be in position to treat coronavirus because of the fundamental threat. We would start lending with easing borrowing terms in the every a part of the planet to overcome from Catastrophe. We would maintain flow of funds in microfinance institutions, by introducing additional capital into them so that these institutions will be in position to lend again and play important and major role in the recovery of economies. Worldwide this industry was built from first to last with cooperative act of venture capitalist, contributors’ decision makers, faculties, researchers, etc to form comprehensive financial services make obtainable to the poor people on earth. We have achieved much together. We now got to deploy as a sector to come out from this catastrophe as e arly as possible and protected the maximized wealth max of the last four decades. The underprivileged persons from all part of planet who presume to take complete financial services such as borrow, save, and transfer money is totally depending on microfinance. Key words: Microfinance, COVID-19, Catastrophe.